Pengaruh Keterlibatan Kerja Karyawan, Karakteristik Pekerjaan dan Dukungan Organisasi Terhadap Komitmen Organisasional Pada Pegawai Dinas Kependudukan dan Pencatatan Sipil Kabupaten Lombok Barat - Asrani Asrani; Djoko Suprayetno; I Nyoman Nugraha (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2024)
This research is entitled the influence of employee work enggagement, job characteristics, and organizational support on organizational commitment in employees of the West Lombok Regency Dukcapil Service. This research aims to determine the influence and significance of the variables employee enggagement, job characteristics and organizational support on organizational commitment at the West Lombok Regency Dukcapil Service. There were 35 respondents, using causal associative research methods, namely research used to see the relationship between variables. The data analysis used was multiple linear regression processed using IBM SPSS and statistical tests were carried out, namely the F test, t test and R Square test. The research results show that: 1). Employee engagement variables have a positive and significant effect on organizational commitment, 2). Job characteristics variables have a negative and insignificant effect on organizational commitment, and 3). The organizational support variable has a positive and significant effect on organizational commitment.